The Relationship Between Coping Strategies and Cigarette Smoking Behavior Among Final-year Engineering Students in Jember, Indonesia - Putri, Maudy Chinthania Ekyta; Noveyani, Adistha Eka; Kinanthi, Citra Anggun (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Many university students, including final-year engineering students in Indonesia, often use cigarette smoking as a coping strategy to manage academic stress and psychological distress, despite its well-documented health risks. Objective: This study aimed to determine the relationship between coping strategy type and smoking Among Final-year Engineering Students at college. Methods:  An analytic study with a cross-sectional approach. The study was conducted in Jember, East Java, from October 2022 to July 2023. The population was 779 engineering students at the University of Jember. The sampling method used was cluster sampling, and the Isaac and Michael formulas obtained 260 samples. Students filled out questionnaires distributed by researchers using the Self-Reporting Questionnaire method through the Google Form platform. Results: Most respondents were male (77%), and more than half were smokers (64.9%). Smoker respondents started smoking at 15-19 years (50,9%). Respondents experienced moderate stress levels (78.5%), and 4,5% experienced high stress levels. As coping stress type, most respondents were problem-focused coping (91,7%), with smoker respondents at 92,4% and non-smoker respondents at 90,3%. This high prevalence of problem-focused coping among both smokers and non-smokers suggests that these students may be equipped with effective strategies for managing stress. There is no association between the type of coping stress and cigarette smoking (p-value: 0,981), indicating that other factors may play a more critical role in influencing smoking habits among this population, such as social influences, peer pressure, or environmental factors that are not captured by the coping strategy framework. Conclusion: Despite finding no association between the type of coping stress and cigarette smoking, the study highlights the prevalent use of problem-focused coping strategies among engineering students, suggesting the need for further research into the complex interplay between stress management and smoking habits among this demographic.